Association of Paternal Workplace and Community Social Capital With Paternal Postnatal Depression and Anxiety: A Prospective Study - Doi, Satomi; Isumi, Aya; Fujiwara, Takeo (Frontiers in Psychiatry, 2022)
Objective: The aim of this study is to examine the association between workplace and community social capital and fathers’ postpartum depression and anxiety three months after delivery in Japan. Methods: Fathers who had babies delivered in two obstetric clinics in Tokyo, Japan were recruited to take part in the study (response rate = 76.2%). Participants completed questionnaires measuring workplace and community social capital, depression, and anxiety at one week and a follow-up at three months post-delivery (N=398). Multiple linear regression analyses were performed with multiple imputation for missing data (at most, n=60, 15.1%). Results: Community social capital was inversely associated with both depressive symptoms (β= -0.21, 95%CI= -0.33 to -0.08) and anxiety (β= -0.38, 95%CI= -0.66 to -0.11) at 3 months, after adjusting for covariates. No association was found between workplace social capital and depressive symptoms and anxiety. Conclusion: Paternal community social capital, but not workplace social capital, was shown to be a preventive factor for paternal depression and anxiety up to three months post-delivery. To prevent paternal mental health problems during the postpartum period, an intervention to promote paternal community, rather than workplace, social capital may be warranted.